THE CURRENT STATUS AND CONSERVATION PROPOSALS OF STRUCTURES AND FOUNTAINS BELONGING TO HAMIDIYE WATER FACILITIES - Uguryol, Drahsan (EGE UNIV, 2020)
Istanbul's last foundation waterway was established by Abdulhamid II under the name of Abdulhamid Khan Hamidiye Water Facilities in order to provide quality drinking water to the city and Yildiz Palace. With the establishment of Hamidiye Water Facilities, pressurized water was started to be provided to the city for the first time. The water brought to the city was distributed to the public by connecting it to some existing fountains on the water pipeline or by building new fountains. The fountains built for Hamidiye Water are extremely elaborate and decorated. In addition, there are fountains made of iron and marble that are identified with Hamidiye Water. It was calculated that water could initially be supplied to about 30 street fountains with the facility which started its service in 1901-1902. However, over time, there were attempts in order to supply water to more places. The buildings and fountains belonging to Hamidiye Water Facilities are important structures of our cultural and industrial heritage. However, some of the buildings and fountains have not survived till today. Those who have survived to the present day have lost their functions as a result of changing living conditions and their relationship with their environment as a result of the change of the traditional texture. Some of Hamidiye Fountains, which possessed the highest artistic taste of the period, have lost their original form as they have been destroyed in time, and others have been relocated. In addition, the losing process of the originality of the fountains still continues today due to many factors such as environmental conditions, faulty repairs with incorrect materials and poor labor and other unconscious interventions. In this study, the current status of the structures of Hamidiye Water Facilities and the fountains, which are an important part of the historical city texture, was investigated. The conservation problems of the existing structures and fountains were determined, and the information on the shape and material properties of the structures and some fountains that have not survived was obtained. In addition, fountains whose locations have changed over time by being removed from the water pipeline and given different names were identified. In line with the findings, conservation proposals were made for the structures and fountains belonging to Hamidiye Water Facilities which have reached the present time.
Keywords: Hamidiye; fountain; conservation problems; cultural property; water structures; Art